A Modest Proposal to Abandon Strict Products Liability - Powers, Jr., William (Cadernos do Programa de Pós-Graduação em Direito – PPGDir./UFRGS, 2014)
In this article Professor Wlliam Powers, Jr. explains why products liability law is currently in disarray and presents a partial solution. To give some order to products liability law, Professor Powers suggests doing away entirely with the doctrine of strict liability. The author asserts that although his plan sounds dramatic, it is really only a "modest proposal." Professor Powers feels the practice of maintaining a distinction between strict products liabillity and negligence has a pernicious effect on personal injury litigation, and that abandoning this distinction will have little irnpact on worthy cases.